Urban crisis: state reform and popular reaction: a case study of Alexandra - Jochelson, Karen Jane (My University, 1988)
This study examines state reform policy and popular township response from 1976 to 1987 in Alexandra, a black township bordering Johannesburg and Sandton's richest white suburbs.
Thesis (B.A. (Hons.))--University of the Witwatersrand, Arts Faculty (Political Science), 1988
Keywords: Housing development--South Africa; Alexandra (Johannesburg, South Africa)--Social conditions--History